Pengaruh Ukuran Perusahaan, Kepemilikan Institusional Dan Komisaris Independen Publik Terhadap Tax Avoidance - Hidayat, Taufik; Ayunita Ajengtiyas , Ayunita Ajengtiyas; Ginting, Rudi (Universitas Djuanda, 2022)
This research aims to determine the effect of firm size, institusional ownership and independent board commissioners on tax avoidance of listed manufacturing companies in Indonesia Stock Exchange in the period 2018 – 2020. The type of this research is quantitative research that uses secondary data based on annual report. A sample of this research consisted of 91 manufacturing companies. Techniques analyzing data in this research used regression model selection test, classical assumption test, multiple linear regression, and partial hypothesis testing (t test). Conclusion of this research that firm size, institutional and control variable (firm age) has no effect on tax avoidance. While independent board commissioners has a negative significant effect on tax avoidance.